1.5 V square‐root domain universal biquad filters. (7th October 2011) - Laoudias, C.; Psychalinos, C.; Stoumpou, E.
ABSTRACT Square‐root domain universal biquad topologies are introduced in this paper. One of them is single input multiple output, while the other one is multiple input single output biquad. Important benefits offered by the proposed topologies are the electronic adjustment of the resonant frequency and the capability for operating in a low‐voltage environment; also, the resonant frequency could be adjusted without disturbing the Q factor and vice‐versa. Simulation results using the Spectre simulator of the Analog Design Environment of Cadence software validate the correct operation of the proposed topologies and provide important performance characteristics. Copyright © 2011 John Wiley & Sons, Ltd.